2008
DOI: 10.1097/pas.0b013e31815a3900
|View full text |Cite
|
Sign up to set email alerts
|

NUT Rearrangement in Undifferentiated Carcinomas of the Upper Aerodigestive Tract

Abstract: Approximately, 20% of UCUAT not associated with EBV infection were found to have rearrangements of NUT by FISH. Although previous reports suggest that NMCs afflict only children and young adults, 4 of 5 of the patients described are mature adults older than any heretofore reported, suggesting that previous reports may have been biased in their case selections. Furthermore, because these tumors are indistinguishable from other poorly differentiated carcinomas, IHC using NUT antibody may be a useful method for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
188
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 214 publications
(198 citation statements)
references
References 22 publications
7
188
0
3
Order By: Relevance
“…NUT, p63 immunohistochemistry, and periodic acid-Schiff (PAS) with and without diastase and mucicarmine histochemistry had been performed previously on corresponding surgical pathology material. 14,15 Patient age, sex, primary tumor site, aspirated site, and original cytologic diagnosis were noted; concise clinical follow-up was obtained. Cases were assessed for the following cytologic features: cellularity, architecture, cytoplasm, cell size, nuclear contours, nucleoli, chromatin, anisonucleosis/cytosis, mitotic activity, background, and nuclear crush.…”
Section: Cancer Cytopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…NUT, p63 immunohistochemistry, and periodic acid-Schiff (PAS) with and without diastase and mucicarmine histochemistry had been performed previously on corresponding surgical pathology material. 14,15 Patient age, sex, primary tumor site, aspirated site, and original cytologic diagnosis were noted; concise clinical follow-up was obtained. Cases were assessed for the following cytologic features: cellularity, architecture, cytoplasm, cell size, nuclear contours, nucleoli, chromatin, anisonucleosis/cytosis, mitotic activity, background, and nuclear crush.…”
Section: Cancer Cytopathologymentioning
confidence: 99%
“…14 Although previous screening attempts had been undertaken in pediatric tumors, our patient population was unselected for age. All 5 tumors involved mature adults, ages 31-78 years, including 4 patients older than any previously reported.…”
mentioning
confidence: 99%
“…Sinonasal tract involvement by NUT carcinoma is much less common than mediastinal disease, but most head and neck cases affect the nasal cavity and paranasal sinuses (65%), with a median presentation in the 20 s, showing a slight female predominance. [67][68][69][70][71][72][73] There is no known etiologic association. Patients present with a rapidlygrowing, extensively destructive mass, often with orbital involvement, and lymph node metastases in about 50% of patients.…”
Section: Nut Carcinoma (Squamous Cell Carcinoma)mentioning
confidence: 99%
“…The neoplastic cells will be positive with pancytokeratin (AE1/AE3), along with CK5/6, p63 and p40, 69,70,75 frequently with CD34 (55%) 76 , and uncommonly with neuroendocrine markers, p16 and TTF-1. By definition, NUTM1 rearrangement must be documented, which can be achieved by strong, diffuse (450%) nuclear staining with the NUT monoclonal antibody (C52, Cell Signaling Technologies, Inc.; Figure 7), 75,77 or by other methodologies (FISH, reverse-transcriptase PCR, targeted next-generation sequencing).…”
Section: Nut Carcinoma (Squamous Cell Carcinoma)mentioning
confidence: 99%
“…Subsequent studies have revealed NC to constitute 18 % of Epstein-Barr Virus (EBV) negative undifferentiated carcinomas of the upper aerodigestive tract, making it a likely under diagnosed tumor entity of the head and neck [7]. Histopathologically, NC is an epithelial neoplasm composed of poorly differentiated basaloid cells with focal squamous differentiation and immunohistochemically positive for cytokeratin 7 (CK7) and p63 [8].…”
Section: Introductionmentioning
confidence: 99%